1993
DOI: 10.1159/000227218
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Mechanisms Involved in the Immunostimulatory Action of the Pineal Hormone in Cancer Patients

Abstract: The mechanisms responsible for the immunostimulatory role of the pineal hormone melatonin (MLT) are still obscure. To investigate the influence of MLT on interleukin-2 (IL-2)-induced immune effects in cancer, we compared the results obtained in 14 cancer patients treated with IL-2 (6 x 106 IU/day s.c. for 5 days/week for 4 weeks) plus MLT (10 mg/day orally) with those seen in 14 patients treated with IL-2 alone and with those obtained from 14 other patients treated with MLT only. All patients were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 8 publications
2
36
0
3
Order By: Relevance
“…It appeared from the study of Karimungi and Joshi (1996) and Karimungi et al (1996) that the effect of melatonin treatment on RBCs count depends on the time of melatonin injection and the time of blood collection. They reported that a single injection of melatonin at 17.00 h for 4 weeks decreased the RBCs, PCV and Hb when samples were collected at 12.00 h, while twice daily injections of melatonin at 9.00 h and 17.00 h increased RBCs, PCV and Hb at 18.00 h. Reverse results were obtained when blood samples were collected at 6.00 h and 24.00 h. Moreover, The increase in RBCs count, PCV and Hb concentration obtained in the present study may be attributed either to its direct stimulatory effect on bone marrow, which was previously reported by Anwar et al (1998) or indirectly through stimulation of some cytokins, which was found to have a powerful stimulatory effect on bone marrow cells proliferation (Lissoni et al, 1993).…”
Section: Discussionsupporting
confidence: 69%
“…It appeared from the study of Karimungi and Joshi (1996) and Karimungi et al (1996) that the effect of melatonin treatment on RBCs count depends on the time of melatonin injection and the time of blood collection. They reported that a single injection of melatonin at 17.00 h for 4 weeks decreased the RBCs, PCV and Hb when samples were collected at 12.00 h, while twice daily injections of melatonin at 9.00 h and 17.00 h increased RBCs, PCV and Hb at 18.00 h. Reverse results were obtained when blood samples were collected at 6.00 h and 24.00 h. Moreover, The increase in RBCs count, PCV and Hb concentration obtained in the present study may be attributed either to its direct stimulatory effect on bone marrow, which was previously reported by Anwar et al (1998) or indirectly through stimulation of some cytokins, which was found to have a powerful stimulatory effect on bone marrow cells proliferation (Lissoni et al, 1993).…”
Section: Discussionsupporting
confidence: 69%
“…Whether the observed effects are mediated through these receptors needs to be studied. Further, studies have also shown that mela tonin has a regulatory role in the proliferation of granulocyte-macrophage colony forming units in rat bone marrow cultures and that pinealectomy causes a drastic reduction in their number [21,22], The clinical studies have reported an increase in the mean lym phocyte numbers in patients suffering from metastatic solid neoplasms when melatonin was given in addition to interleukin-2 [27], In the light of these observations, the present findings are important and support the view that melatonin has a role in the regulation of neutrophil and lymphocyte activities. This is possibly the first investigation on the in fluence of melatonin on hematological param eters with reference to diurnal changes in the various blood components.…”
Section: Discussionmentioning
confidence: 99%
“…T-helper cells play a crucial role in protection against malignancy. In addition, studies performed in patients with cancer have documented that immunological treatment with IL-2 plus melatonin induces a significant increase in the number of NK cells [77]. Therefore, the oncostatic actions of melatonin can also include direct augmentation of NK cell activity [2].…”
Section: Modulation Of the Immune Responsementioning
confidence: 99%